Assessment of the cost of material costs of citizens for preparation for implementation of VFSK standards «ready for labor and defense» (based on the example of student youth of Barnaul) - Podberezko N.A.; Samsonov I.I.; Kuznetsova E.D.; Iskakova G.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the cost of preparation for compliance with the standards of the All-Russian Sports Society for GTO (using the example of student youth in Barnaul). Methods and structure of the study. A survey of Barnaul students was conducted, an analysis of the resources of electronic sporting goods stores, as well as statistical data on the level of wages of the population of the Altai Territory in 2023. Results and conclusions. It was revealed that 62,5% of students prefer to buy sportswear and shoes in the Sportmaster chain stores, 44,9% of students prefer Nike. The cost of such goods is 32-149% (men’s range) and 53-136% (women’s range) of the average wage of the population of the Altai Territory in November 2023, which amounted to 44 042 rubles per month in November 2023. To reduce the cost of clothing and footwear in preparation for the implementation of the VFSK GTO, it is necessary to develop such a product under the «GTO» brand, which, in turn, will create a new or expand the existing production of clothing and footwear, increase the number of new jobs, as well as promote and advertising of VFSK GTO. In order to increase the motivation of young people in physical education and sports, it is proposed to more actively implement social order tools for physical education and health services and (or) consider the issue of introducing an additional tool - the «Lesgaft Card».